Perception and attitudes towards epilepsy: point of view of professionals allied to medicine from Mobile Emergency Service in Campinas - Fernandes,Paula T. (2009)
INTRODUCTION: Epilepsy is very prevalent in our society, but unfortunately lack of knowledge is still very common, contributing to psycho-social difficulties to people with epilepsy. PURPOSE: The aim of this study was to assess the epilepsy' perception and attitudes by professionals of emergency medical service in Campinas, Brazil. MATERIAL AND METHODS: This study was carried out with professionals of SAMU-192, who participated on the VII Stroke Workshop of Campinas in November 2007. RESULTS: One hundred-forty nine (149) professionals answered the questionnaire (49% women, average age of 37 years, range from 21 to 59 year). Ninety (60%) were professionals allied to medicine (nurses, health auxiliary, dentists), six (4%) were physicians and 53 (36%) were other professions (secretary, driver). In overall, a great majority of the subjects had an appropriate knowledge regarding epilepsy. But, some beliefs are still present. In relation to epilepsy' perception, some wrong ideas appeared, as epilepsy is a contagious disease, people with epilepsy can not practice physical exercise or to work. Also, the doubts regarding pregnancy and treatment of epilepsy were observed. Regarding attitudes during an epileptic seizure, some inadequate attitudes appeared: to put something in patient's mouth, to restrict the patients' movements or give something strong to smell (alcohol or vinegar) in order to stop the seizure. CONCLUSION: In this context, it is necessary a continuous education programs to the allied health professionals to improve the perception and attitudes, bringing epilepsy out of the shadows.